(untitled) (Mustansiria Dental Journal, 2018)
Background: The aim of this study is to determine the relative influence of diabetes mellitus on periodontal parameters and to correlate between glucose content of saliva and blood in diabetics and non diabetics Material and method: Total samples composed of 105 participants. Group I composed from 35 healthy subjects, group II composed from 35 patients were well controlled diabetics and 35 patients were moderately and poorly controlled diabetics. The periodontal parameters which included Plaque Index (PL.I) and gingival index (G.I) were recorded. Whole saliva samples were collected for determination of glucose and total protein. Results: The mean value of glucose in saliva was higher in group II (1.769±0.972) and in group III (4.054±2.851) compared to group I (0.993±0.331). Inter group comparison for PL.I showed that there was a significant difference between group I and group II, while was no significant difference between group II and group III at P-value>0.05. The mean G.I in group II and group III were elevated compared with group I. There was weak or no correlation between periodontal and biochemical parameters. Conclusion: Diabetic groups showed significant difference in periodontal parameters compared to control group with significant difference between group II and group III. Also significant increase in glucose and total protein of saliva in diabetic groups compared to control group.